Obesity and Type 2 Diabetes Prevalence in Adults from Two Remote First Nations Communities in Northwestern Ontario, Canada - Pascal Imbeault; François Haman; Jules M. Blais; Shinjini Pal; Tim Seabert; Eva M. Krümmel; Michael A. Robidoux (Journal of Obesity)
Objective. To assess the prevalence rates of obesity and type 2 diabetes in adults from two First Nations communities in northwestern Ontario, Canada. Methods. Body weight, height, and waist circumference as well as fasting and postprandial glucose levels following an oral glucose tolerance test were measured in 31 men and 41 women. Results. The mean age of the sample was 43 ± 13 y. The prevalence of obesity was 65.3% and was comparable between men and women. 90.3% of the individuals presented waist circumference levels greater than the thresholds associated with an increased risk of developing health problems. 26 of the 72 individuals (36.1%) were found to be type 2 diabetic. The prevalence of diabetes was not different between men and women. Conclusion. Using objective measurements, this study confirms that First Nations adults from remote communities of Canada continue to experience a disproportionately higher prevalence of obesity and type 2 diabetes than nonaboriginal Canadians.